2016
DOI: 10.1016/j.ijheh.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Potential health risk of allergenic pollen with climate change associated spreading capacity: Ragweed and olive sensitization in two German federal states

Abstract: Spread of ragweed and particularly olive may result in prompt occurrence of allergic symptoms. Early identification of invasive allergens due to climate change does need time and spatial close meshed measurement of respective indicator allergens and sensitization pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Additional published data from 18 countries were included from a European-wide trend study concerning Ambrosia pollen (Sikoparija et al, 2017). Further data were included from studies conducted in Germany (Buters et al, 2015;Höflich et al, 2016;Melgar et al, 2012), Croatia (Bokan et al, 2007;Liu et al, 2016;Menut et al, 2014;Peternel et al, 2006;Puljak et al, 2016), Turkey (Acar et al, 2017;Altintaş et al, 2004;Bicakci and Tosunoglu, 2015;Tosunoglu and Bicakci, 2015), Romania (Leru et al, 2018), Russia (Severova et al, 2015;Shamgunova and Zaklyakova, 2011), Serbia (Josipović and Ljubičić, 2012), Ukraine (Maleeva and Prikhodko, 2017;Rodinkova, 2013;Turos et al, 2009), Bosnia (Turos et al, 2009) and Slovakia (Hrabovský et al, 2016). All these sites are located within urban zones and data are collected from the top of a building, typically 10 m-20 m above ground level.…”
Section: Pollen Data and Calculation Of Infestation Levelmentioning
confidence: 99%
“…Additional published data from 18 countries were included from a European-wide trend study concerning Ambrosia pollen (Sikoparija et al, 2017). Further data were included from studies conducted in Germany (Buters et al, 2015;Höflich et al, 2016;Melgar et al, 2012), Croatia (Bokan et al, 2007;Liu et al, 2016;Menut et al, 2014;Peternel et al, 2006;Puljak et al, 2016), Turkey (Acar et al, 2017;Altintaş et al, 2004;Bicakci and Tosunoglu, 2015;Tosunoglu and Bicakci, 2015), Romania (Leru et al, 2018), Russia (Severova et al, 2015;Shamgunova and Zaklyakova, 2011), Serbia (Josipović and Ljubičić, 2012), Ukraine (Maleeva and Prikhodko, 2017;Rodinkova, 2013;Turos et al, 2009), Bosnia (Turos et al, 2009) and Slovakia (Hrabovský et al, 2016). All these sites are located within urban zones and data are collected from the top of a building, typically 10 m-20 m above ground level.…”
Section: Pollen Data and Calculation Of Infestation Levelmentioning
confidence: 99%
“…Pollen concentration and distribution already may be changing due to a positive correlation with climate change. Studies have shown a correlation between carbon dioxide, temperature, and pollen production, where CO2 concentrations, ambient temperature, and allergenic production are all positively related (Hoflich et al 2016). Climate can affect the biological and chemical components of pollen by altering the shape, density, size, or vitality of pollen particles in the environment (Makra et al 2014), potentially leading to greater susceptibility in humans.…”
Section: Introductionmentioning
confidence: 99%
“…If the species richness of allergenic plants changes, the various pollen allergens could then impact populations more severely. As the maximum pollen count a human is exposed to increases, the intensification in total allergenic inhalation could heighten severity of respiratory symptoms (Hoflich at al. 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Global warming may also lead to prolongation of the pollen season [14][15][16] and occurrence of new allergens [17] in temperate zones, rendering asthma therapy and control more difficult in affected patients. Importantly, pollen is also increasingly found in regions that used to be nearly free of pollen, like higher altitudes in the Alps [18].…”
Section: Introductionmentioning
confidence: 99%